Research Trends and Hotspots on Montessori Intervention in Patients With Dementia From 2000 to 2021: A Bibliometric Analysis - Zhou, Ting; Qu, Jiling; Sun, Huiping; Xue, Mengxin; Shen, Yijing; Liu, Yongbing (Frontiers in Psychiatry, 2021)
Background: Patients with dementia experience a variety of neuropsychiatric symptoms and behavioral disturbances. The Montessori method is a type of non-pharmacological intervention to care for people with dementia. However, there are few bibliometric studies on the application of Montessori methods. We aimed to analyze the hotspots and trends of research on the application of Montessori methods to the care of dementia patients. Methods: Microsoft Office Excel, Co-Occurrence 9.9, and CiteSpace were used to analyze the articles on Montessori intervention in patients with dementia from 2000 to 2021 in China National Knowledge Infrastructure, Wanfang, China Science and Technology Journal Database, Web of Science core collection database, PubMed, and Scopus. Results: A total of 23 Chinese language publications and 113 English language publications were included. The number of English language publications was on the rise, while the number of Chinese language publications was low. There are many issuing institutions which published articles in this field, mostly concentrated in universities. English language publication sources were more than Chinese language publication sources. The hot research topic in Chinese language publications and English language publications was the care of agitated behavior of dementia patients based on the Montessori method. The psychological problems of dementia patients are likely to become a hot issue of concern for scholars in Chinese. There will be a lot of research focusing on dementia patients and their family caregivers in this field. Conclusion: The bibliometric and visualization analysis helps us understand the current research status and hotspots of Montessori intervention in dementia patients in Chinese language publications and English language publications.